Kualitas Angkutan, Waktu Distribusi dan Keselamatan Kerja Peserta Bela Negara Non-Militer - Ahmad Jaenudin; Denny Langas Siahaan; Suparwan Cecep Kosasih; Husni Hasan (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
The purpose of this study is to find out the effect of transportation quality, time distribution, and work safety on the satisfaction of non-military state defense participants in “Jayakarta” Military Command (Komando Daerah Militer Jayakarta / KODAM Jaya) in 2019. The main problems found were the quality of transportation, in this case TNI-AD trucks, which are expected to receive proper attention and care; late distribution in the process; work safety related to the vehicles’ condition; and lack of supervision of non-military state defense participants. Structural Equation Modeling (SEM) method and variance-based Smart PLS was used to test the hypothesis. Respondents were non-military state defense participants in ”Jayakarta” Main Regiment Unit with a total sample of 100 people. Based on the results of the study, work safety is able to mediate the quality of transportation and time distribution to the non-military state defense participants’ satisfaction. The key findings are the lack of transportation facilities and infrastructure, time distribution that does not run based on the schedule and limited number of medical personnel on work safety equipment during non-military state defense training.